Mangrove associated macrobenthos community structure from an estuarine island - MD. HABIBUR RAHMAN; M. BELAL HOSSAIN; Ahasan Habib; MD. ABU NOMAN; SHUVAGATO MONDAL (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rahman MDH, Hossain MB, Habib A, Noman MDA, Mondal S. 2021. Mangrove associated macrobenthos community structure from an estuarine island. Biodiversitas 22: 247-252. Macroinvertebrate living on or around the mangroves has not been or less investigated in Bangladesh. This study was carried out to describe the density, distribution, and community structure of mangrove associated macrobenthos in Nijhum Dwip, central coast of Bangladesh. A total of 17 taxa were identified belonging to mainly Polychaetes (67.37%), Mysids (23.53%), Isopods (3.83%), Amphipods (0.58%), and Gastropods (0.29%). Polychaetes were dominant by contributing 67.37% of total macrobenthos. The number of benthic fauna ranged from 359 to 1617 inds./m2 with a mean value of 1003.93± 400.3 inds./m 2 There was no significant difference observed (p > 0.05) in the abundance of macrofauna among the stations. The maximum Shannon-Wiener Index (H’) of species diversity was found at St2 (1.323) and the lowest at St4 (0.8) in the monsoon period possibly due to high rainfall and disturbance of benthic habitat. The Shannon-Wiener diversity values suggest the area was less polluted. The information from the present study can be used to measure the impacts of pollution to conserve biodiversity in sustainable manner.